Creativity, Bipolar Disorder Vulnerability and Psychological Well-Being: A Preliminary Study. Issue 1 (2nd January 2017) - Gostoli, Sara; Cerini, Veronica; Piolanti, Antonio; Rafanelli, Chiara
Abstract : The aim of this research was to investigate the relationships between creativity, subclinical bipolar disorder symptomatology, and psychological well-being. The study method was of descriptive, correlational type. Significant tests were performed using multivariate regression analysis. Students of the 4th grade of 6 different Italian colleges ( N = 329) completed voluntarily the test of divergent feelings (TDF) included in the creative assessment packet (CAP), the Temperament Evaluation of Memphis, Paris, Pisa and San Diego—Autoquestionnaire (TEMPS-A), and the psychological well-being scale (PWB). Significant positive correlations between creativity and bipolar disorder vulnerability, especially hyperthymia, were found. Creativity was, instead, poorly associated to psychological well-being subscales, except autonomy and personal growth. In addition, although multivariate regression showed that creativity was not a significant predictor of almost all the psychological well-being subscales, it did show a significant association with personal growth. On the contrary, bipolar disorder vulnerability, in particular hyperthymia, was found to significantly predict all psychological well-being scales, except personal growth. These results improve knowledge on the mutual association of creativity, psychological well-being, and bipolar vulnerability, giving a theoretical framework in which situate these constructs.